Toxoplasma gondii in experimentally infected Bos taurus and Bos indicus semen and tissues - Scarpelli,Leslie (2009)
Eighteen young steers were inoculated with Toxoplasma gondii and randomly distributed into three groups of six animals each: GI, 2.5x10(5) "P" strain oocysts, GII, 5.0x10(6) "RH" strain tachyzoites, and GIII (Control). Clinical, serological and parasitemia exams were realized. Parasite investigation by bioassay and PCR was realized on semen and fragments of skeletal musculature, lymph nodes, brain, retina, spleen, liver, lung, testicle, epididymis and seminal vesicle. Blood and semen samples were collected on days -2, -1, 1, 3, 5, 7, 14 and weekly thereafter, up to postinfection day (PID) 84. The inoculated steers (GI and GII) presented hyperthermia from PID 3 to 16. Antibodies against T. gondii were detected through the indirect fluorescence antibody test (IFAT) on PID 5 (1:16) in both inoculated groups (oocysts and tachyzoites), reaching peaks of 1:4096 on PID 7. Parasitemia outbursts occurred in all infected bovines, principally from PID 7 to 28, independent of the strain and inoculate used. Bioassays revealed the presence of parasites in semen samples of animals infected with oocysts (GI) and tachyzoites (GII) on several experimental days between PID 7 and 84. Tissue parasitism by T. gondii was diagnosed by bioassay and the PCR technique in several organ and tissue fragments. These findings suggest the possibility of sexual transmission of T. gondii in the bovine species.